2021
DOI: 10.1038/s41598-021-90398-x
|View full text |Cite
|
Sign up to set email alerts
|

EGCG promotes PRKCA expression to alleviate LPS-induced acute lung injury and inflammatory response

Abstract: Acute lung injury (ALI), which could be induced by multiple factors such as lipopolysaccharide (LPS), refer to clinical symptoms of acute respiratory failure, commonly with high morbidity and mortality. Reportedly, active ingredients from green tea have anti-inflammatory and anticancer properties, including epigallocatechin-3-gallate (EGCG). In the present study, protein kinase C alpha (PRKCA) is involved in EGCG protection against LPS-induced inflammation and ALI. EGCG treatment attenuated LPS-stimulated ALI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 54 publications
1
36
1
1
Order By: Relevance
“…IL-6 and TNF are common markers of inflammation. EGCG protects against LPS-induced lung injury by promoting PRCKA and inhibiting the expression of IL-6 and TNF ( Wang et al, 2021 ). EGCG protects the myocardium of streptozotocin-nicotinamide-induced diabetic rats through anti-inflammatory and anti-apoptotic pathways, mainly through diminishing the levels of IL-6, TNF-α and Caspase3 ( Othman et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 and TNF are common markers of inflammation. EGCG protects against LPS-induced lung injury by promoting PRCKA and inhibiting the expression of IL-6 and TNF ( Wang et al, 2021 ). EGCG protects the myocardium of streptozotocin-nicotinamide-induced diabetic rats through anti-inflammatory and anti-apoptotic pathways, mainly through diminishing the levels of IL-6, TNF-α and Caspase3 ( Othman et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…TRQ significantly decreased the number of inflammatory cells (neutrophils and macrophages) in lung and reduced MPO activity which was produced by neutrophils. The inflammatory mediators, including TNF-α, IL-1β, IL-6, and IFN-β, are closely associated with the exaggeration of ALI ( Wang M. et al, 2021 ). Our results showed that TRQ remarkably reduced TNF-α, IL-1β, IL-6, and IFN-β production in BALF of ALI mice and LPS-stimulated RAW 264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…As a bioactive dietary component, EG owns a great many pharmacological actions including antioxidation, anti-inflammation, antifibrosis, and inhibiting endoplasmic reticulum stress [ 16 18 ]. In acute lung injury induced by sepsis, acute pancreatitis, paraquat, and hip fracture, EG treatment could exert vital protective roles by different mechanisms [ 19 22 ]. In transverse aortic constriction-induced cardiac fibrosis, EG treatment significantly decreased collagen deposition and cardiomyocyte hypertrophy by blocking AKT/mTOR pathway [ 18 ].…”
Section: Introductionmentioning
confidence: 99%